2012
DOI: 10.1039/c2dt11805j
|View full text |Cite
|
Sign up to set email alerts
|

Mono- and dinuclear ruthenium(ii) 1,6,7,12-tetraazaperylene complexes

Abstract: We report the synthesis of free 1,6,7,12-tetraazaperylene (tape). Tape was obtained from 1,1'-bis-2,7-naphthyridine by potassium promoted cyclization followed by oxidation with air. Mono- and dinuclear ruthenium(II) 1,6,7,12-tetraazaperylene complexes of the general formulas [Ru(L-L)(2)(tape)](PF(6))(2), [1](PF(6))(2)-[5](PF(6))(2), and [{Ru(L-L)(2)}(2)(μ-tape)](PF(6))(4), [6](PF(6))(4)-[10](PF(6))(4), with{L-L = phen, bpy, dmbpy (4,4'-dimethyl-2,2'-bipyridine), dtbbpy (4,4'-ditertbutyl-2,2'-bipyridine) and tm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
72
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(76 citation statements)
references
References 40 publications
4
72
0
Order By: Relevance
“…The potential difference ΔE = 410 mV and the intervalence-charge-transfer (IVCT) transition at 2472 nm indicate a high degree of electronic interaction between the two ruthenium ions mediated through the tape bridging ligand. Monoreduced species [1] + , [2] + , and [3] 3+ yield EPR signals indicating that the unpaired electron is mainly centered on the "large surface" ligands dape or tape. The second reduction in each complex and the second oxidation in [3] 4+ prove to be irreversible in these spectroelectrochemical experiments.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The potential difference ΔE = 410 mV and the intervalence-charge-transfer (IVCT) transition at 2472 nm indicate a high degree of electronic interaction between the two ruthenium ions mediated through the tape bridging ligand. Monoreduced species [1] + , [2] + , and [3] 3+ yield EPR signals indicating that the unpaired electron is mainly centered on the "large surface" ligands dape or tape. The second reduction in each complex and the second oxidation in [3] 4+ prove to be irreversible in these spectroelectrochemical experiments.…”
Section: Introductionmentioning
confidence: 99%
“…The second reduction in each complex and the second oxidation in [3] 4+ prove to be irreversible in these spectroelectrochemical experiments. [2] Both dinuclear complexes [{Ru(bpy) 2 } 2 (μ-BL)] 4+ (BL = dbneil, [5] tape [2] ) exhibit two well-resolved reversible metal-centered oxidations in their cyclic voltammograms, indicating significant metal-metal interactions mediated by the conjugated bridging ligands. characterized by spectroelectrochemical methods.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…66, it was reported that 1,6,7,12-tetraazaperylene (TAPE) 69 molecules at the edges of self-assembled islands grown on Ag(111) can be deliberately switched in their charge state with the electric field from a scanning-probe tip. The selfassembled islands formed at room temperature have a periodic structure, in which each molecule is rotated by roughly Θ = 80 • with respect to its four neighbors.…”
Section: Summing Up Previous Workmentioning
confidence: 99%